2000
DOI: 10.1073/pnas.150236297
|View full text |Cite
|
Sign up to set email alerts
|

Rapid restoration of visual pigment and function with oral retinoid in a mouse model of childhood blindness

Abstract: Mutations in the retinal pigment epithelium gene encoding RPE65 are a cause of the incurable early-onset recessive human retinal degenerations known as Leber congenital amaurosis. Rpe65-deficient mice, a model of Leber congenital amaurosis, have no rod photopigment and severely impaired rod physiology. We analyzed retinoid flow in this model and then intervened by using oral 9-cis-retinal, attempting to bypass the biochemical block caused by the genetic abnormality. Within 48 h, there was formation of rod phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(254 citation statements)
references
References 44 publications
17
234
1
1
Order By: Relevance
“…Van Hooser et al (5) reported that the small a-waves that could be recorded in the Rpe65 Ϫ/Ϫ mice under bright light conditions were characterized by low photoreceptor sensitivity with no obvious change in gain of the photoreceptor transduction cascade or temporal characteristics. In a follow-up study using single-cell recordings (6), they demonstrated that Rpe65 Ϫ/Ϫ rods have responses greatly reduced in sensitivity and amplitude, whereas kinetics were similar to, but slightly faster than, WT kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Hooser et al (5) reported that the small a-waves that could be recorded in the Rpe65 Ϫ/Ϫ mice under bright light conditions were characterized by low photoreceptor sensitivity with no obvious change in gain of the photoreceptor transduction cascade or temporal characteristics. In a follow-up study using single-cell recordings (6), they demonstrated that Rpe65 Ϫ/Ϫ rods have responses greatly reduced in sensitivity and amplitude, whereas kinetics were similar to, but slightly faster than, WT kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…The photoreceptors of Rpe65 Ϫ/Ϫ mice are almost completely depleted of 11-cis-retinal, the native ligand of cone and rod opsins, resulting in minimal levels of rhodopsin and the deterioration of their photosensitivity (4). Photoreceptor function has been shown to be partially restored by supplying exogenous ligand (5,6). Thus, the Rpe65 Ϫ/Ϫ mouse is an excellent model in which to study the two key factors that control the activity of rhodopsin, the supply of the ligand (7,8) and the level of rhodopsin/opsin phosphorylation.…”
mentioning
confidence: 99%
“…As in vitamin A-deprived rats and humans, the sensitivity can be rapidly restored by treatment with supplemental chromophore. (42)(43)(44)(45) Rods in Rpe65 À/À mice behave as if in the presence of a continuous background light. (46) Light responses are only a fraction of their normal amplitude and show an accelerated turn-off, characteristic of light-adapted photoreceptors (see Ref.…”
Section: Continuous Light Kills By Activating Transductionmentioning
confidence: 99%
“…These retinols are stored in the form of retinyl esters before use. Because 9-cis-retinal is more stable than 9-cis-retinol, an alternative pathway in the production of 9-cis-isomers is the isomerization of all-trans-retinol to 9-cis-retinol (43). Although the equilibrium is shifted toward the all-trans-isomers (5), small amounts of 9-cis-retinal would be trapped as it is formed and further oxidized by aldehyde dehydrogenases (44).…”
Section: Involvement Of Rdh11-14 In Retinoid Transformation and All-tmentioning
confidence: 99%